Evaluation on Merauke Drainage System in Overcoming Flood-Prone Areas - Ramdhani, Bagoes Rezky; Pratama, Maryo Inri; Wisaksono, Anggoro (President University, 2023)
Merauke city suffers flooding in almost every rainy season, which endangers the environment and disturbspeople's activities. One of the worst floods happened in 2019, where flooding damaged vegetables and crops, impactedthe city's economy, and later caused economic inflation. Therefore, a study evaluating the drainage system in Meraukecity is needed to overcome this issue. This study was conducted through a field survey and literature study with datathat varies from hydrological, elevation, and hydraulics data. Hydrological data includes yearly rainfall data, andhydraulics data consists of the drainage network and designs. This evaluation will then result in the normalization of adrainage system. This study found that the capacity of the current drainage system is 10.815 m3/s, where this drainagecapacity cannot accommodate the amount of flood discharge plan. Also, the existing drainage system is missing acomponent that was not built in the first place, affecting the drainage's capacity. Therefore, a normalization of thedrainage system is needed to avoid flooding.